(untitled) (Biological Sciences - PJSIR, 1996)
Anincubationexperimentwasconductedinthelaboratoryto studytheeffectofmoistureandwheatstrawamend- ment on the mineralization and transformationof phenyl-t’C cyfluthrin (activeingredientof Baythroid, aninsecticide manufactured by Bayer AG, Leverkusen, Germany) into differentsoil fractions.The treated soil was incubated at40, 60 or 100%water holding capacity (WHC) moisture and with or without wheat straw amendment. After 18weeks of incubation, 44-58% of the cyfluthrin-r’Cwas lost fromthesoil asCOr Mineralizationof cyfluthrin was more rapid in unamended soilandatlowermoistureregimes;themaximumbeingat40%WHC.Inunamendedsoil,ahigherpropor-. tion of the applied 14Cwas found in forms extractable with methanol (anefficient solvent of cyfluthrin). In amended soil, on theother hand,a greaterproportionoftheadded14Cwasfoundinbound formsi.e.,fulvic acid,humic acid and humins. Transformation of cyfluthrin-v’Cinto stable humic compounds was more intense at lower moisture regimes. However, in all treatments, a higher proportion of bound residues extractable with alkali was present in fulvic acid fraction.